Implementation of Ethereum-Based Blockchain Technology for ADS-B Data Security and Validation - Rabbaniansyah, Kgs Muhammad Farhan; Lindawati, Lindawati; Soim, Sopian (ITEJ (Information Technology Engineering Journals), 2026)
Automatic Dependent Surveillance–Broadcast (ADS-B) has significantly enhanced air traffic monitoring by enabling real-time broadcasting of aircraft positions and identifiers. However, its lack of cryptographic safeguards makes it inherently vulnerable to spoofing, replay, and tampering attacks. This study presents a blockchain-based ADS-B validation framework that leverages Ethereum smart contracts and MetaMask for secure, decentralized data authentication. The proposed system validates incoming flight messages by enforcing logical constraints on altitude changes, timestamp order, and geographic displacement using Solidity-coded rules. Each data transaction is subject to a dual-layer security model: automated detection by the smart contract and manual authorization via MetaMask. This ensures that even flagged anomalies cannot be committed without human approval, thus combining operational oversight with blockchain's immutability. The system was tested using flight data from the OpenSky Network, with 56 attack simulations performed across spoofing, replay, and tampering categories. The contract achieved a 92.9% detection rate, with all accepted anomalies intentionally approved to test forensic transparency. Ethereum’s transparent ledger preserved all transaction details, reinforcing its potential for regulatory compliance and incident investigation. The results affirm blockchain’s suitability in protecting aviation telemetry against unauthorized modifications. Future enhancements may include machine learning for anomaly detection, stricter timestamp controls, and integration with global aircraft registries to improve spoofing detection. This implementation bridges theoretical blockchain benefits with operational air traffic requirements.